Translation, Adaptation And Validation Of The Bulgarian Version Of The SIDAED Questionnaire - Rumyana Kuzmanova; Irina Stefanova; Irena Velcheva; Katerina Stambolieva (Journal of Biomedical & Clinical Research, 2015)
The aim of the study is the translation, adaptation and validation of Side effects of antiepileptic drugs questionnaire in Bulgarian language (SIDAED-BG) in order to use it for objective monitoring of patients with epilepsy. One hundred and thirty one patients (mean age 40.13±13.37 years) took part in the investigation. The internal consistency and test-retest reliability were tested by Cronbach's α and ICC estimations. The convergent construct validity was evaluated by estimating the correlation of SIDAED-BG with the QOLIE-89 and the discriminant validity - by evaluation of the difference between SIDAED-BG scores and clinical parameters such as type of epilepsy using Kruskal-Wallis ANOVA. The Cronbach's α of the total scale was 0.93. The test-retest reliability was higher and determined the strong positive correlations between the first and second examination. The SIDAED-BG questionnaire showed good internal consistency (Cronbach's alpha ranged from 0.37 to 0.86) and the scores significantly correlated with other questionnaires such as QOLIE-89 and showed a good discriminative validity between groups with different levels of self-assessed adverse effects of antiepileptic drugs. The Bulgarian version of SIDAED is a reliable and valid tool in assessing the patient-reported adverse effects of antiepileptic drugs and their impact on the patient's outcome.